Pengaruh Penambahan Limbah Ekstraksi Buah Kelapa Sawit Terhadap Pembuatan Paving Block - Wahyu Setiawan; Alex Kurniawandy; Ermiyati Ermiyati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The waste of palm know as waste of palm oil extraction, which is recently available abundantly. One of efforts in using this waste material is as additive in paving block industry. This research presents the efficiency of waste of palm oil extraction as an additive material of paving block at optimum mix composition regarding the paving block compressive strength, absorption and resistance to chemicals.The composition of waste of palm oil extraction was 0%, 2,5%, 5%, 7,5%, 10% and 12,5% by weight of cement. Research results showed that the use of waste of palm oil extraction as an additive affect the quality of the paving block. The best composition of paving block in this research was the amount of waste of palm oil extraction can be added to paving block as much as 7,5%. It was shown from the value of compressive strength of 7, 14, and 28 days increased to reach 18,3 MPa, water absorption is 5,9%, and resistant to sodium sulfate. Based on SNI 03-0691-1996, paving block generated from this treatment fitted in C quality of paving block and can be used for parking area.Keywords: waste of palm oil extraction, paving block